Moisture Dependent Engineering Properties of Onion Seeds - Pandiselvam, R.; Pragalyaashree, M. M.; Kailappan, R.; Thirupathi, V.; Krishnakumar, P. (Journal of Agricultural Engineering, 2014)
Some important physical, frictional and aerodynamic properties of aggregatum onion seed (variety CO 5) were determined as a function of moisture content in the range of 9.8 to 29.6 % (d.b). Physical, frictional and aerodynamic properties namely size, shape, 1000 seed mass, bulk density, true density, porosity and angle of repose increased with increase in moisture content. Terminal velocity and static coefficient of friction on various surfaces, namely,plywood, mild steel, galvanized iron and stainless steel also increased linearly with increase in moisture content. Plywood surface offered maximum friction and stainless steel recorded minimum values.